Integration of Demonstration Methods for Memorizing Short Surahs in the Merdeka Belajar Curriculum at Aisyiyah Bustanul Athfal Kindergarten, Langkat - Pani; Amini, Nur Rahmah; Tanjung, Ellisa Fitri (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2024)
This study aims to analyze the implementation of the demonstration method in memorizing short surahs at TK Aisyiyah Bustanul Athfal, Langkat Regency, and its integration into the Merdeka Belajar Curriculum. This research used in the form of an in-depth case study to understand how demonstration methods are applied and integrated into the curriculum, as well as to identify the challenges and impacts of the application of these methods on students' skill skills.The results of the study indicate that the demonstration method, applied with thorough preparation and structured implementation, is effective in improving students' memorization abilities. Students find it easier to memorize short surahs with concrete examples given by the teacher. Observations and documentation reinforce these findings, with students showing enthusiasm and active involvement in the demonstrations. The integration of the demonstration method into the Merdeka Belajar Curriculum provides teachers with the flexibility to choose teaching methods that suit students' needs, creating a more dynamic and enjoyable learning environment. Periodic evaluations show a significant improvement in students' memorization abilities, proving the effectiveness of this method in helping students memorize short surahs.